G-D’s Physics Points at the “End of Time”: “Perfected Geulah State” of the Universe!? - Bentovish, Jehonathan (European Journal of Applied Sciences, 2023)
Twenty-First Century Theoretical Physics is undergoing a profound “Paradigmatic-Shift” from the Old “Material-Causal” Paradigm of 29th Century’s General Relativity Theory (GRT) & Quantum Mechanics (QM) to the New “G-D’s Physics” (“Computational Unified Field Theory”, CUFT)! This profound “Paradigmatic-Shift” ensues from the preceding “Paradigmatic Crisis” of the Old Paradigm – signified by the “theoretical inconsistency” between its two “pillars”, e.g., GRT & QM, and its inability to account for the accelerated expansion of the physical universe, assumed to be “caused” by an “undetectable” purely hypothetical “Dark-Matter” concept (assumed to comprise up to 95% of all matter, but which failed to be detected experimentally for the past two decades)?! In contrast, the New “G-D’s Physics” Scientific Paradigm discovered a singular higher-ordered “Universal Computational/Consciousness Principle” (UCP) which simultaneously computes all exhaustive spatial pixels (in the universe) at the incredible rate of “c2/h” = 1.36-50 (sec’), which creates an extremely rapid series of “Universal Frames” (UF’s) comprising the entire physical universe at every “minimal time-point”! Based on “G-D’s Physics” discovery of the UCP and associated “Universal Computational Formula” which completely unifies (for the first time in Physics) between the four basic physical features of “space” and “energy”, “mass” and “time”, it provides us with an alternative explanation for the origin- sustenance- (“dissolution”)- and “development” of the entire physical universe: towards an “Ultimate Perfected Guelah State” of the universe! In the current article, direct empirical validation of two (unique) “Critical Predictions” of this New “G-D’s Physics” Scientific Paradigm is outlined which therefore provides science with an alternative (satisfactory) explanation for the accelerated expansion of the universe based on this singular UCP’s “Collective Human Consciousness Focus Hypothesis” Postulate, and points at the feasibility of a new (exciting) conception of the UCP’s “steering” of the universe towards an “End of Time: Perfected Geulah State”, in which Science (and Humanity) will recognize the “Singularity”, ”All-Goodness”, “Morality”, ”Peace” and “Harmony” characterizing this singular UCP, as well as Humanity’s “Perfected Geulah” State!